High formation of superoxide anion and nitric oxide, and matrix metalloproteinases activity in vascular wall of rectal carcinoma vessels - Burlaka, A.P.; Sidorik, E.P.; Ganusevich, I.I.; Lestchenko, Yu.M.; Burlaka, A.А.; Osinsky, S.P. (Experimental Oncology, 2006)
Aim: To study the relationship between the level of generation of reactive oxygen species (ROS) and nitric oxide (NO) and activity of matrix metalloproteinases (MMPs) MMP-2 and MMP-9 in the vessels isolated from rectal tumors and Arteria rectalis superior. Methods: EPR at the room temperature and 77 °K, Spin Traps technology and zymography in polyacrylamide gels were applied. Results: In the vessels isolated from rectal tumors and Arteria rectalis superior high levels of ROS, NO· and formation of complexes of NO· with FeS-proteins at the sites of electron-transporting chain of mitochondria have been detected. High activities of MMP-2 and MMP-9 in vascular wall were also observed. The direct positive correlation between the rate of NO· generation and formation of complexes of NO·· with FeS-proteins as well as between ROS and NO formation and MMPs activities have been revealed. Conclusion: Altered oxidative equilibrium in mitochondria of cells in vascular wall promotes formation of cell hypoxia and its autocatalytic potentiation accompanied with activation of MMPs.